PENGAWASAN KEPATUHAN PERPAJAKAN WAJIB PAJAK STRATEGIS DI KPP PRATAMA SUKOHARJO - Fanuel Felix Christian; Irwan Aribowo (JURNAL PAJAK INDONESIA, 2021)
Taxpayer compliance must be concerned about considering the amount of tax contribution to state revenue. This study aims to determine supervision activities of Strategic Taxpayer compliance and the steps that can be done to improve the supervision of Taxpayers compliance in KPP Pratama Sukoharjo. This research used a descriptive approach with qualitative research methods. The data used was primary data related to supervision activities of tax compliance. Supervision activities of Strategic Taxpayer compliance, such as, analysis of financial statements, SP2DK issuance, visitation, warning letters issuance, tax collection letters issuance, and use of the Approweb application. The steps to improve supervision of taxpayer compliance for instance, massive taxation socialization, integration of taxation data, and implementation of specific supervision programs was carried out to face obstacles, challenges, and improve taxpayer compliance.